Casein Kinase 1δ Inhibitors as Promising Therapeutic Agents for Neurodegenerative Disorders - Catarzi, Daniela; Varano, Flavia; Vigiani, Erica; Lambertucci, Catia; Spinaci, Andrea; Volpini, Rosaria; Colotta, Vittoria (Current Medicinal Chemistry, 2022)
Casein kinase 1 (CK1) belongs to the serine-threonine kinase family and is expressed in all eukaryotic organisms. At least six human isoforms of CK1 (termed α, γ1-3, δ and ) have been cloned and characterized. CK1δ isoform modulates several physiological processes, including DNA damage repair, circadian rhythm, cellular proliferation and apoptosis. Therefore, CK1δ dysfunction may trigger diverse pathologies, such as cancer, inflammation and central nervous system disorders. Overexpression and aberrant activity of CK1δ have been connected to hyperphosphorylation of key proteins implicated in the development of neurodegenerative disorders, such as Parkinson’s and Alzheimer’s diseases and Amyotrophic Lateral Sclerosis. Thus, CK1δ inhibitors have attracted attention as potential drugs for these pathologies and several compounds have been synthesized or isolated from natural sources to be evaluated for their CK1δ inhibitory activity. Here we report a comprehensive review on the development of CK1δ inhibitors, with a particular emphasis on structure-activity relationships and computational studies, which provide useful insight for the design of novel inhibitors.
Keywords: small molecules